2015
DOI: 10.1016/j.trsl.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

A disintegrin and metalloprotease-10 is correlated with disease activity and mediates monocyte migration and adhesion in rheumatoid arthritis

Abstract: A disintegrin and metalloproteases (ADAMs) are a family of proteins that have been reported to be involved in several inflammatory conditions. We examined the secretion of ADAM-10 in biological fluids from patients with rheumatoid arthritis (RA) and the role it plays in monocyte migration. ADAM-10 levels were measured using enzyme-linked immunosorbent assays and immunofluorescence. To examine the role of ADAM-10 in RA synovial fluids (SFs), we studied THP-1 (human acute monocyte leukemia cell line) and monocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Indeed, the putative substrates of ADAM9, ADAM10 and ADAM17 identified by MS in CSF fluid, according to MEROPS, include amyloid beta A4 protein (Table S1, Supporting Information), supporting its involvement in AD pathogenesis. These ADAM proteases were already assessed in body fluids, mostly in blood‐derived ones, with ELISA approaches, and related with other pathological conditions besides AD …”
Section: Comparative Analysis Of Proteases Distribution Among Distincmentioning
confidence: 99%
“…Indeed, the putative substrates of ADAM9, ADAM10 and ADAM17 identified by MS in CSF fluid, according to MEROPS, include amyloid beta A4 protein (Table S1, Supporting Information), supporting its involvement in AD pathogenesis. These ADAM proteases were already assessed in body fluids, mostly in blood‐derived ones, with ELISA approaches, and related with other pathological conditions besides AD …”
Section: Comparative Analysis Of Proteases Distribution Among Distincmentioning
confidence: 99%
“…ADAM (a disintegrin and metalloproteases) is a family of proteases that release a variety of membrane proteins; it has been reported that ADAM-10 is responsible for releasing different chemokines, like CXCL16 and CX3CL1 [55]. Isozaki et al in 2015 reported that the levels of ADAM-10 in serum from RA patients were significantly higher compared to healthy controls by ELISA; this correlated with the disease activity measured by DAS28 (disease activity score of 28).…”
Section: Endothelial Alterations In Sle and Ra: Potential Contribumentioning
confidence: 99%
“…These findings were corroborated with the fibroblast-like synoviocytes from patients, which were transfected with specific siRNA (small interfering RNA) to ADAM-10 transcription; the silencing of this gene in vitro inhibited the monocyte and synoviocyte adhesion to the endothelial cells and decreased growth factor and production of CX3CL1. These results suggest that ADAM-10 plays an important role in the monocyte adhesion to inflamed tissues from RA patients and that it could be involved in the endothelial alteration of these patients [55]. …”
Section: Endothelial Alterations In Sle and Ra: Potential Contribumentioning
confidence: 99%
“…ADAM10 is also overexpressed in the synovial tissue of RA patients (95). It has been reported that ADAM10 is correlated with disease activity and regulates monocyte migration and adhesion in RA patient fluids (96,97). ADAM10 elevation in specific cells or tissues correlates strongly with various disease states.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrate that ADAM10 is upregulated in endothelial cells and synovial lining fibroblasts in RA tissue biopsies compared to osteoarthritis and healthy patients (95). Additionally, in vitro studies reveal that siRNA knockdown of ADAM10 impairs angiogenesis and suppresses VEGF release in endothelial cell lines (95,96). Administration of this siRNA in vivo in a murine model of collagen-induced arthritis improved arthritis symptoms and reduced serum levels of the angiogenic cytokine VEGF (97).…”
Section: Rheumatoid Arthritismentioning
confidence: 99%